Policy Evaluation of Regional Tax Contributions to the Improvement of Regional Original Revenue in East Java Province - Andika Indra Prasetyo; Dandy Wirawan; Kristyan Dwijosusilo; Kresna Adhi Prahmana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
This study evaluates the policy contribution of regional taxes — specifically Motor Vehicle Tax (PKB) and Motor Vehicle Transfer Tax (BBNKB) — to the improvement of Regional Original Revenue (PAD) in East Java Province for the period 2020 to 2024. Using a descriptive quantitative approach with secondary data obtained from the Regional Revenue Agency (Bapenda) of East Java Province, the study analyzes the realization of tax revenues and their percentage contributions to PAD. Evaluation results indicate that PKB consistently contributes significantly to PAD with an average of 43.78%, categorized as highly contributing. Meanwhile, BBNKB demonstrates a fairly stable contribution averaging 22.74%, categorized as moderately contributing. Policy evaluation reveals that both tax instruments serve as the primary backbone of local revenue, supporting fiscal autonomy and strengthening regional development capacity. Several policy challenges were identified, including the impact of the COVID-19 pandemic, tax amnesty policies, and varying levels of taxpayer compliance. This study recommends that the regional government optimize local tax strategies through service digitalization, intensified taxpayer education, and adaptive policy formulation to ensure sustainable PAD growth.